Translation Method in Translating Agatha Christie's Indonesian Version novel 'Kucing di Tengah Burung Dara - Harmit Kaur; Rahmad Husein; Anni Holila Pulungan (RIRAI Publisher, 2024)
This study deals with eight translation methods applied in translating in Agatha Christie’s Indonesian Version Novel ‘Kucing di Tengah Burung Dara’. This study attempts to describe the eight methods namely: Word for Word Translation, Literal Translation, Faithful Translation, Semantic Translation, Adaptation Translation, Idiomatic Translation and Communicative Translation. The research methodology is qualitative. The dominant method in translating the novel is Communicative Translation so it gives the readers the same impact as the original does.